"To Avoid Embarrassment, Poetry Should Keep Itself to Itself": An Autoethnographic Exploration of the Place of Poetry in Adult Literacy Teacher Education (LEARNing Landscapes, 2010)
This paper explores the reasons for the author’s reluctance to bring examples of her own poetry into her practice as teacher educator on a program for adult literacy tutors. The paper begins with the author’s poem, "The Place of Poetry," which is used as a tool for reflection on the author’s assumptions about her identities as poet and as educator. The paper ends with poems written by the author’s students, which demonstrate that the use of poetry in education has the potential to facilitate transformative learning.
Keywords: poetry; teacher educator; adult literacy; education; trasformative learning; autoethnography